Perlindungan Hukum terhadap Hak Merek Perusahaan di Kota Makassar - Ariadin; Basri; Aries Maulana (PT PUSTAKA CENDEKIA GROUP, 2024)
This study aims to examine the legal protection of corporate trademark rights in Makassar. Several questions that are the focus of this study include: 1) What are the procedures applicable to trademark registration in Makassar? 2) How are sanctions applied to violations of corporate trademark rights there? The approach used is qualitative with a legal method. Data sources include interviews with judges at the Makassar District Court as primary data, and regulations, books, journals, and online articles as secondary data. The data are analyzed qualitatively, with the aim of providing a clear and systematic picture to then be concluded. The results of the study indicate that inaccuracy in trademark examination by the Directorate General of Intellectual Property Rights (Dirjen HKI) causes confusion and losses for trademark owners and registrants. In addition, the application of sanctions is more often focused on criminal and civil aspects, although administrative sanctions, such as termination of trademark use, should be enforced more firmly.